Adsorption of dark coloured compounds from peach pulp by using powdered-activated carbon - Arslanoglu, FN; Kar, F; Arslan, N (Elsevier Sci Ltd, 2005)
The potential of powdered-activated carbon (PAC) for the adsorption of dark coloured compounds from peach pulp was studied at different PAC concentrations (0.5, 1, 3, 5 kg PAC per m(3) peach pulp) and for the temperature range of 20-60 degrees C. The isotherm studies were carried out to evaluate the effect of adsorbent dosage, contact time and initial absorbance. For equilibrium adsorption curves, the Langmuir, Freundlich, Temkin and Frumkin models were attempted by using the absorbance data at 420 nm and model parameters were obtained for different temperatures. The results clearly showed that the adsorption data of dark coloured compounds present in peach pulp onto PAC fits well to the Langmuir and Temkin models having correlation coefficients higher than 0.90 at all temperatures. Five kinetic models including the first-order equation, second-order equation, the modified Freundlich, the pore diffusion model and the Elovich equation were tested to follow the adsorption processes. Results of the kinetic studies show that the adsorption reaction was well represented by the Elovich model. The activation energy of adsorption was found to be 13.79 kJ/mol. The low activation energy indicated that the adsorption reaction was also diffusion controlled. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: peach pulp; powdered-activated carbon; adsorption; kinetic models